(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Surrogacy in Portugal have been down a bumpy road. After a situation of legal uncertainty, in 2006 the law came to prohibit it, even criminally. In 2016 an innovative law was enacted, allowing surrogacy under very strict conditions, but the Constitutional Court declared the law unconstitutional and null. Following that ruling, the Parliament amended the law. It addressed every concern of the Court, except for the right of the surrogate to withdraw from the contract, so this regulation was again considered unconstitutional. The surrogate’s right to regret has become a sine qua non for the legitimacy of surrogacy in Portugal.